GPS-mælingar við Eyjafjallajökul frá goslokum 2010 - Ólafur Páll Jónsson 1989- (2013)
During the pre-eruptionphase and subsequent eruptions in Eyjafjallajökull in 2010,considerable crustal deformation was measured around the volcano. By conducting GPS-measurements at certain points around the volcano, it is possible to see what kind of deformation has been occurring since the eruption ended if any. GPS-measurements from 2001-2009 show a low but systematic pattern. They were used to correct newer measurements conducted after the end of the eruption. During the first weeks after the eruption there was a clear sign of deflation, with most stations moving relatively fast towards the center of Eyjafjallajökull. After the first few weeks the deformation rate slowed down. The stations STE2 og THEY showed the fastest movement, with both stations moving away from the volcano. This might indicate in flation. Talsverðar jarðskorpuhreyfingar mældust í kringum Eyjafjallajökul í tengslum við eldgos í Eyjafjallajökli 2010 og aðdraganda þess. Til að komast að því hvort skorpan sé enn á hreyfingu eftir gos má meðal annars notast við GPS mælingar á mælipunktum sem eru umhverfis jökulinn. Á tímabilinu 2001-2009 voru tiltölulega litlar jarðhræringar við Eyjafjallajökul og því voru GPS mælingar frá því tímabili bornar saman við mælingar sem gerðar voru eftir gosið. Niðurstöður mælinganna sýna að mælipunktarnir hreyfast hratt í átt að miðju jökulsins fyrstu vikurnar eftir gos en eftir það hefur hraðinn verið mun minni. Stöðvarnar STE2 og THEY hafa sýnt áberandi færslu frá fjallinu frá síðari hluta ársins 2010, en það gæti bent til þenslu í fjallinu.